COMPREHENSIVE ENDODONTIC MANAGEMENT OF AN ELLIS CLASS IV FRACTURE WITH ASYMPTOMATIC APICAL PERIODONTITIS - Arnila Ayu Prahesti Istikhomah; Salma Mei Asti; Christina Mahardika (Fakultas Kedokteran Gigi Unjani, 2026)
Traumatic dental injuries to anterior teeth frequently result in pulpal necrosis and periapical pathology. Root canal treatment (RCT) is required for complicated crown fractures with pulpal exposure in order to eliminate intracanal infection and promote periapical healing. Proper diagnosis and a multidisciplinary treatment approach are required to restore both function and appearance, especially in the anterior region. This case report describes the comprehensive management of an Ellis Class IV fracture in a 47-year-old female patient who had asymptomatic apical periodontitis. A clinical examination revealed extensive crown structure loss in the maxillary left central incisor, as well as a fracture that penetrated the pulp chamber. Pulp vitality testing revealed no response from the tooth. Radiographic examination revealed widening of the periodontal ligament space, indicating apical inflammation. A multi-visit RCT protocol was implemented. Chemomechanical preparation of the root canal system was followed by the administration of calcium hydroxide as an intracanal medicament to improve disinfection. After adequate canal debridement, a hermetic seal was created by obturating with gutta-percha and an endomethasone-based sealant. Post-endodontic rehabilitation involved placement of a fiber-reinforced composite post to improve retention and distribute occlusal forces, followed by composite core build-up. The definitive restoration was achieved with a porcelain-fused-to-metal crown to restore function and esthetics. Clinical follow-up demonstrated absence of symptoms, negative percussion response, and satisfactory functional stability, indicating successful treatment outcome and favorable short-term prognosis. DOI : 10.54052/jhds.v6n1.p111-126